6(x-8)+9=3(x-7)

Simple and best practice solution for 6(x-8)+9=3(x-7) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(x-8)+9=3(x-7) equation:


Simplifying
6(x + -8) + 9 = 3(x + -7)

Reorder the terms:
6(-8 + x) + 9 = 3(x + -7)
(-8 * 6 + x * 6) + 9 = 3(x + -7)
(-48 + 6x) + 9 = 3(x + -7)

Reorder the terms:
-48 + 9 + 6x = 3(x + -7)

Combine like terms: -48 + 9 = -39
-39 + 6x = 3(x + -7)

Reorder the terms:
-39 + 6x = 3(-7 + x)
-39 + 6x = (-7 * 3 + x * 3)
-39 + 6x = (-21 + 3x)

Solving
-39 + 6x = -21 + 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.
-39 + 6x + -3x = -21 + 3x + -3x

Combine like terms: 6x + -3x = 3x
-39 + 3x = -21 + 3x + -3x

Combine like terms: 3x + -3x = 0
-39 + 3x = -21 + 0
-39 + 3x = -21

Add '39' to each side of the equation.
-39 + 39 + 3x = -21 + 39

Combine like terms: -39 + 39 = 0
0 + 3x = -21 + 39
3x = -21 + 39

Combine like terms: -21 + 39 = 18
3x = 18

Divide each side by '3'.
x = 6

Simplifying
x = 6

See similar equations:

| 7(-7+6k)=371 | | 4(7t+10)=40 | | 3(5-7x)=-132 | | 2(7n-8)=12 | | (-4n-3n)x-8= | | 3(r+2)=-1(24-12) | | (9x^2/10)*(7/10x) | | 2+5=65-2x | | 6(2-2w)=-12 | | 5(3-3b)=15 | | 4(2t+9)=-28 | | 6(1a+4)=30 | | 56+12(x)=80+8(x) | | (16x^2-5)-(4x^2+10)= | | 4(1n+5)=20 | | 11=6/7^3x | | 4(7m-2)=-8 | | 5x+18=6x+12 | | 4(-3x-3)=-120 | | .75m+32=47 | | 7(3w-4)=-238 | | 2(8-w)=32 | | 3(-5w+3)=129 | | 7(-7t-7)=539 | | 3(6+5t)=-117 | | 6-8x-3=-66+6x-15 | | 5x+22=3+8x-5 | | 1/5(7y-2)+1/10(6y+7) | | 7(-2n+5)=77 | | 70+27x+2=180 | | 2(1x+6)=34 | | 8n^2-13n+5= |

Equations solver categories